Understanding educators’ perspectives and experiences of COVID-19 in schools serving children with intellectual/developmental disabilities - Jones, Erin F.; Singh, Vini; Holingue, Calliope; Errichetti, Cheryl Lyn; Myers, Linda; Sherby, Michael R.; Gurnett, Christina; Newland, Jason; Kalb, Luther (Frontiers in Education, 2022)
The COVID-19 pandemic has significantly impacted educators, both personally and professionally. However, very little is known about the extent of these impacts among educators’ serving children with intellectual and developmental disabilities (IDD). The present study surveyed 230 educators (teachers, staff, and administrators) to assess their wellbeing, concerns during the pandemic, and perceived importance of various COVID-19 school mitigation strategies. Data were gathered May/June of 2021 from two separate school districts, one in the Midwest and the other in the Mid-Atlantic, serving children with IDD. Nearly half of all survey respondents reported poor wellbeing. Almost all educators reported health of themselves, students, and family members was their greatest concern when compared to pandemic-related disruption of their duties or benefits (e.g., not having enough sick time). Most educators felt disinfecting routines, vaccinations, and daily health checks were the most helpful in preventing the spread of COVID-19 in schools, while in-school mask mandates and weekly testing of students and staff were perceived as less helpful. Our findings suggest that efforts are needed to support the wellbeing of educators during these challenging times. When pandemic-related policies and procedures are decided by administrators, our data suggest educators will review decisions within the framework of health and safety of themselves, their students, and families. Understanding this framework may be particularly valuable when considering implementation of COVID-19 policies, like masking and COVID-19 testing, that are less preferred.